2016
DOI: 10.1002/mabi.201600033
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Light Tunable Tissue Adhesive Dendrimers

Abstract: Development of bioadhesive formulations for tissue fixation remains a challenge. The major drawbacks of available bioadhesives are low adhesion strength, toxic byproducts, and complexity of application onto affected tissues. In order to address these problems, this study has developed a hydrogel bioadhesive system based on poly amido amine (PAMAM) dendrimer, grafted (conjugated) with UV-sensitive, 4-[3-(trifluoromethyl)-3H-diazirin-3-yl] benzyl bromide (PAMAM-g-diazirine). This particular diazirine molecule ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 52 publications
1
78
0
Order By: Relevance
“…Biomaterials with strong adhesive properties to wet tissues have emerged as promising strategies for sutureless wound closure following surgical procedures [49]. In this regard, in our previous studies, we demonstrated that GelMA-based hydrogels possess high adhesive strength to various physiological tissues, while also exhibiting superior mechanical performance when compared with commercially available tissue adhesives [37,50].…”
Section: Adhesive Properties Of Gelma/bio-il Cardiopatches To Physiolmentioning
confidence: 92%
“…Biomaterials with strong adhesive properties to wet tissues have emerged as promising strategies for sutureless wound closure following surgical procedures [49]. In this regard, in our previous studies, we demonstrated that GelMA-based hydrogels possess high adhesive strength to various physiological tissues, while also exhibiting superior mechanical performance when compared with commercially available tissue adhesives [37,50].…”
Section: Adhesive Properties Of Gelma/bio-il Cardiopatches To Physiolmentioning
confidence: 92%
“…Diazirine generates highly reactive carbene when irradiated with ultraviolet A (UVA, 365 nm) light, which can insert itself into most CH bonds . Polymer end‐modified with diazirine exhibited light‐initiated adhesion, effectively adhered PLGA films to biological tissues . The bulk mechanical property and adhesive property of the diazirine‐modified adhesive can be tuned by the dose of applied UVA.…”
Section: Multifunctional Biomedical Adhesivesmentioning
confidence: 99%
“…By grafting TAD onto G5 PAMAM dendrimer, a model system is easily synthesized in a one‐step reaction to explore photochemical and bioadhesive structure–activity relationships. Previous investigations have explored PDz with respect to grafting/solid content, voltage‐activation, and non‐aqueous formulations . Previous studies have also focused on biocompatibility and cytotoxicity behavior of the primary components.…”
Section: Comparison Of Energy Generated Per Pulse Versus Required Actmentioning
confidence: 99%